THE EFFECT OF FIRM SIZE, PROFITABILITY, LEVERAGE AND BOARD SIZE ON DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY IN COMPANY’S ANNUAL REPORTS - Wagiu, Frily Ansyelia; Mekel, Peggy A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The important aspect in economics that has to be considered by company when reached achivement in expending their business in Global competition is corporate social responsibility or CSR, many manufactured companies listed on Indonesia stock exchange who have been taken advantages from public environment. This study tries to prove the importance of CSR disclosure by using four variables: firm size, profitability, leverage and board size that have been tested in previous researches which predicted by author will give positive result on CSR disclosure. Research method that had been used for this research is associateed with multiple linear regression analysis technique. The sample in this study is a company listed on the Indonesia Stock Exchange (BEI) in the year 2005 to 2008, published in the Indonesian Capital Market Directory (ICMD) 2009-2012 and data collection method obtained through the website owned by BEI, ie www.idx.co.id, BEI in Mega Mas Manado and in Faculty of Economics, Sam Ratulangi University and Indonesian Capital Market directory (ICMD). The result of this research shows positive impact of firm size and board of commisioner size and negative impact of profitabilty and leverage on CSR disclosure partialy. Therefore, company should consider about the CSR Disclosure since it is the most crucial part of the company and how the company should revealed their self to the public. Keywords: firm size, profitabilty, leverage